Hak Waris Transgender Menurut Hukum Positif Di Indonesia - Aurelia Lulu Heny Salsabila; Fatahullah Fatahullah; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2023)
There will surely be new legal challenges as a result of the existence of transgender people in society who are granted judicial recognition of their gender identity, including inheritance law. In order to investigate how transgender people fit into Indonesia's inheritance system and examine the distribution system, this study on transgender inheritance rights according to positive legislation in Indonesia was conducted. This is due to the fact that Indonesian laws and regulations do not yet clearly address transsexual inheritance rights.In this study, legal research and conceptual analysis were combined as part of the research technique. The method of data collecting includes an examination of the literature. Qualitative analysis was the technique employed in this study to examine legal texts. The research's conclusions show that, following the local customary ceremony, a transgender person's inheritance rights and entitlements under customary law will be acknowledged. However, under Islamic law, transgender people are eligible for inheritance if their gender transition is founded on legitimate Islamic justifications. While under civil law, transgender people's inheritance rights are unaffected by their gender.